1986
DOI: 10.1128/mcb.6.12.4419
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of PRT1, a gene required for the initiation of protein biosynthesis in Saccharomyces cerevisiae.

Abstract: We isolated a cloned DNA fragment containing PRTI, a gene required for the initiation of protein biosynthesis in Saccharomyces cerevisiae, by complementation of the temperature-sensitive prtl-l mutation. The entire PRT1 gene is contained within a 3.2-kilobase-pair segment of the cloned DNA in YEpl3 H1.2. Southern blot analysis demonstrated that PRTI is a single copy gene which is transcribed into a 2.3-kilobase RNA. We determined the direction of transcription and mapped the 5' and 3' ends of the gene.The init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…This location is consistent with the results of Keierleber et al (31), who mapped the prt1-1 mutation upstream of position 2220 by integrative transformation. The same study also suggested that, in the absence of gene conversion, the prt1-1 mutation lies upstream of position 1052; our findings indicate that gene conversion may indeed have occurred during that work.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This location is consistent with the results of Keierleber et al (31), who mapped the prt1-1 mutation upstream of position 2220 by integrative transformation. The same study also suggested that, in the absence of gene conversion, the prt1-1 mutation lies upstream of position 1052; our findings indicate that gene conversion may indeed have occurred during that work.…”
Section: Discussionsupporting
confidence: 82%
“…Transcription of the PRT1 gene was found to initiate downstream of the first in-frame ATG of the ORF. This result is consistent with earlier work that localized PRT1 transcription initiation to a region 0.57 kbp upstream of the internal XbaI site (31). The first 39 codons of the PRT1 ORF are therefore not translated; the translation start site is most likely encoded by the second in-frame ATG.…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of the p110 cDNA Deduced Protein-Comparison of the predicted amino acid sequence of p110 subunit of mammalian eIF3 with protein sequences in the Swiss Prot Data Bank revealed that p110 has 32% identity and 56% similarity with the yeast S. cerevisiae protein Prt1p (25,26). The 82.7-kDa yeast Prt1p protein was shown to be a subunit of yeast eIF3 (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…The restriction map of the area 5' to SRA5 that is deleted from pW2 and pW3 (Fig. la) matches the restriction map of PRTJ (19). These data indicate that SRA5 is tightly linked to PRTJ on the right arm of chromosome XV, with the start codon of SRA5 approximately 0.6 kb downstream from the transcription termination site of PRT1.…”
mentioning
confidence: 51%